Targeting pyruvate kinase M2 for the treatment of kidney disease - Chen, Dan-Qian; Han, Jin; Liu, Hui; Feng, Kai; Li, Ping (Frontiers in Pharmacology, 2024)
Pyruvate kinase M2 (PKM2), a rate limiting enzyme in glycolysis, is a cellular regulator that has received extensive attention and regards as a metabolic regulator of cellular metabolism and energy. Kidney is a highly metabolically active organ, and glycolysis is the important energy resource for kidney. The accumulated evidences indicates that the enzymatic activity of PKM2 is disturbed in kidney disease progression and treatment, especially diabetic kidney disease and acute kidney injury. Modulating PKM2 post-translational modification determines its enzymatic activity and nuclear translocation that serves as an important interventional approach to regulate PKM2. Emerging evidences show that PKM2 and its post-translational modification participate in kidney disease progression and treatment through modulating metabolism regulation, podocyte injury, fibroblast activation and proliferation, macrophage polarization, and T cell regulation. Interestingly, PKM2 activators (TEPP-46, DASA-58, mitapivat and TP-1454) and PKM2 inhibitors (shikonin, alkannin, compound 3k and compound 3h) have exhibited potential therapeutic property in kidney disease, which indicates the pleiotropic effects of PKM2 in kidney. In the future, the deep investigation of PKM2 pleiotropic effects in kidney is urgently needed to determine the therapeutic effect of PKM2 activator/inhibitor to benefit patients. The information in this review highlights that PKM2 functions as a potential biomarker and therapeutic target for kidney diseases.